K-Means Clustering Untuk Pengenalan Buah Berdasarkan Karakteristik Warna Citra - Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2011)
Research on pattern recognition in images has been developed. Objects can be recognized by color, texture, or shape. This study took four types of fruit as its object of apple, pear, bark, and orange. Feature extraction image taken based on the color characteristics of objects in the image of Hue Saturation Value. Characteristic images obtained were classified using k-means clustering. This experiment using 20 data has resulted in 70% accuracy. Keyword: feature extraction, Hue Saturation Value, k-means clustering, recognized of fruit